The Effects of nurse-managed ambulatory care (NMAC) on satisfaction of care among patients with rheumatic heart disease (RHD) at the Philippine Heart Center - Aldea, Maria Romina G.
This study mainly examined the effects of nurse-managed ambulatory care (NMAC) on satisfcation of care among RHD patients, who come for their follow-up care at the Outpatient Department (OPD) of Philippine Heart Center. This study was conducted: (1) to determine if NMAC improved activities of daily living, perception of care and physiologic variables among RHD patients; (2) to determine if sociodemographic data, namely, age, sex, education and support system were significantly related to activities of daily living, perception of care and physiologic variables; and (3) to determine the responses of RHD patients to NMAC. The post-test only control group design was utilized. A total of sixty-five (65) patients participated in the study through simple random sampling. Of these, thirty-two (32) patients belonged to the control group and thirty-three (33) patients belonged to the intervention group. The intervention involved direct nursing care consisting of physical assessment, patient education, nurse-patient interaction, and indirect nursing care which included coordination and referral.